Emery de Gaál, O Lord, O seek Your Countenance. Explorations and Discoveries in Pope Benedict XVI’s Theology - Beyga, Paweł (Teologia w Polsce, 2020)
Recenzja książki: Emery de Gaál, O Lord, O seek Your Countenance. Explorations and Discoveries in Pope Benedict XVI’s Theology.